2021
DOI: 10.1128/spectrum.00972-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Recent Tuberculosis Exposure Using QuantiFERON-TB Gold Plus, a Multicenter Study

Abstract: Contact tuberculosis tracing is essential to identify recently infected people, who therefore merit preventive treatment. However, there are no diagnostic tests that can determine whether the infection is a result of a recent exposure or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The study was conducted among a total of 686 adults who were either contacts of microbiologically confirmed-TB patients (high risk), asylum seekers or people from abroad (intermediate risk) and individuals screened for TB infection prior to immune-suppressant therapy for immune-mediated inflammatory disease (low risk). There was a lack of association between an antigen tube differential ≥ 0.6IU/ml and the likelihood of recent TB exposure both in unadjusted and adjusted analyses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted among a total of 686 adults who were either contacts of microbiologically confirmed-TB patients (high risk), asylum seekers or people from abroad (intermediate risk) and individuals screened for TB infection prior to immune-suppressant therapy for immune-mediated inflammatory disease (low risk). There was a lack of association between an antigen tube differential ≥ 0.6IU/ml and the likelihood of recent TB exposure both in unadjusted and adjusted analyses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study could not show an association with recent TB infection, as specific information on TB exposure or risk factors and data on LTBI serial testing were not available. It has recently been reported that QFT-Plus cannot distinguish between recent and past infections, suggesting that it should not be used for contact tuberculosis tracing 23 . This might indicate the need for further evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the presence and strength of the CD8 response may help the clinical assessment of patients with new or active infections as it is usually shut off in old and not active diseases [ 47 ]. Nonetheless, some studies have failed to confirm the relationship between a high CD8 response and recent Mtb infection [ 48 ].…”
Section: Screening Tests For Tbimentioning
confidence: 99%
“…In mycobacterial infections, IFN-γ released by CD4 + T cells is essential for host survival and enhances both CD4 + and CD8 + T cell activities [ 129 ]. However, false-negative IGRA results were detected in patients with TB infection with advanced age [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , …”
Section: Evaluation Of Host-derived Biomarkersmentioning
confidence: 99%